Development and performance tests of a separator for removal of physically emulsified and free oils from wastewaters - Law, Puong Ling; Ngu, Lock Hei; Wong, Kien Kuok; Awangku Abdul Rahman, Pgn. Hj. Yusof (The Institution of Engineers, Malaysia, 2006)
A novel oil-water separator with multiple angles parallel coalescence frustums for removal of physically emulsified and free oils from wastewater was recently developed. Performance tests had been carried out to determine its removal efficiency. The primary component of the separator includes a series of inverted and upright frustums-shaped coalescence plates to form a multiple angle plate arrangement for enhance gravity separation and coalescence of oil droplets. The oil removal efficiency (E) of this separator was found to be inversely proportional to influent flowrate (Q) and directly proportional to retention time, t. The efficiency (E) of this separator can be expressed as a function of flowrate (Q), retention time (t), and influent oil concentration (Coil) by a series of power equations; E = 59.689Q-0.107 for Coil = 100 mg/L, E = 70.753Q-0.1269 for Coil = 1000 mg/L, and E = 40.16t0.127 for Coil = 1000 mg/L. For Coil = 100 mg/L, E could be best expressed by polynomial equation, i.e., E = 0.0001t2 + 0.0045t + 57.147. The highest achievable oil-water separation efficiency of this separation system was approximately 82.4% at a flowrate (Q) of ≤ 5x10-6 m3/s, and retention time of ≥ 4.80 hours. It was found that the presence of an outlet baffle component for the separator could improve oil removal efficiency by approximately 12.9% as compared to without an outlet baffle.